Coronary disease, cardioneuropathy, and conduction system abnormalities in the cardiomyopathy of Friedreich's ataxia. Issue 5 (May 1987) - James, T N; Cobbs, B W; Coghlan, H C; McCoy, W C; Fisch, C
Abstract : Abnormalities of the heart are a frequent and possibly ubiquitous problem in patients with Friedreich's ataxia, but their pathogenesis is unclear. Postmortem findings are reported from the hearts of three patients with Friedreich's ataxia who died of congestive heart failure and atrial arrhythmias. Particular attention was paid to the following: the large and small coronary arteries, the nerves and ganglia, the conduction system, and the histological and cellular features of the cardiomyopathy. There were pleomorphic nuclei and focal fibrosis and degeneration throughout each heart including the conduction system. There were distinctive abnormalities of both large and small coronary arteries, and focal degeneration of nerves and ganglia. These observations suggest a mosaic concept for the pathogenesis for the cardiomyopathy of Friedreich's ataxia that involves the interplay of molecular faults, cardiomyopathy, cardioneuropathy, and coronary disease.